Math know-how : answers to your most persistent teaching issues, grades 3-5 - Adams, Thomasenia Lott; LaFramenta, Joanne (Corwin, a Sage Company, 2014)
With mathematics curriculum mandates constantly evolving and expectations for student achievement on the rise, teachers are under pressure to bring math to life in the classroom and engage their students in meaningful, relevant ways. This book equips teachers with the know-how they need to make this a reality. In this teacher-friendly guide, Adams and LaFramenta demystify the Common Core State standards in mathematics and provide answers to some of the most common questions they have encountered in their years of working in the field as coaches. Chock-full of examples and vignettes, this book will empower maths teachers with the tools and knowledge they need to improve their instruction and increase their students' understanding of key mathematical concept.